2004
DOI: 10.1590/s1516-93322004000100005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da automedicação na população urbana portuguesa

Abstract: Este estudo transversal teve como objetivo principal determinar a prevalência da automedicação em meio urbano. Decorreu nas cidades de Lisboa e Porto, respectivamente em 11 e 15 farmácias, no período de Novembro de 1995 a Setembro de 1996. A recolha de informação dividiu-se em 6 fases de 10 dias cada. A prevalência da automedicação encontrada foi de 26,2%. Encontraram-se diferenças estatisticamente significativas no que respeita às prevalências da automedicação por sexo, idade, nível educacional e atividade pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 2 publications
(1 reference statement)
0
8
0
5
Order By: Relevance
“…Divergent results were found among other studies: in Spain, a higher frequency of self-medication was found among women (p<0.001) (5) ; in Portugal, a significant association was found among people with an average age of 46 years old between self-medication and gender and it was most prevalent among men (p<0.031) (15) ; in Chile, a study carried out with individuals of an average age of 39.8 years old, did not find significant association between these variables (10) .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Divergent results were found among other studies: in Spain, a higher frequency of self-medication was found among women (p<0.001) (5) ; in Portugal, a significant association was found among people with an average age of 46 years old between self-medication and gender and it was most prevalent among men (p<0.031) (15) ; in Chile, a study carried out with individuals of an average age of 39.8 years old, did not find significant association between these variables (10) .…”
Section: Discussionmentioning
confidence: 65%
“…In Portugal, 50% of the medication used in self-medication was recommended by a pharmacist and 1.4% by a nurse (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Self-medication is a worldwide phenomenon, the prevalence of such can differ depending on the population studied, the method and the recall period employed: in Germany 9 , the prevalence for medication use on a self-medication basis was 27.7%; in Portugal 14 , this was 26.2%; in Spain 7 , 12.7%; in Cuba 8 , 7.3%; in Athens-Greece 2 , 23.4%; in the Catalonia region of Spain 20 , 34.0% among men and 25.0% among women; and in Pondicherry-India 22 , this was equal to 11.9%.…”
Section: Introductionmentioning
confidence: 95%
“…Além dos possíveis efeitos colaterais e consequências aos usuários, o uso incorreto e irracional de medicamentos pode ocasionar prejuízos ao sistema público de saúde. Os sintomas iniciais podem ser mascarados, o que prejudica o adequado diagnóstico e agrava futuramente o quadro clínico do paciente 1,4,[6][7][8][9][10][11][12][13][14] . Observou-se 74,5% do total dos entrevistados faziam o uso de medicamentos sem prescrição médica, sendo este percentual semelhante a outros estudos.…”
Section: Discussionunclassified
“…Além disso, para se conseguir uma consulta por meio do Sistema Único de Saúde (SUS), observa-se uma demora que pode perdurar dias e/ou até meses, levando-os à opção do uso de medicamentos sem prescrição médica 6,[15][16][17] . A maioria dos indivíduos entrevistados informou que buscava orientações de farmacêuticos, em balcões de farmácias, para o uso de medicamentos, relatando a dificuldade à acessibilidade e assistência aos hospitais públicos para conseguirem consulta com um médico.…”
Section: Sintomasunclassified